2012
DOI: 10.1523/jneurosci.5835-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Activity Unmasks Dopamine D2 Receptor Modulation of a Specific Class of Layer V Pyramidal Neurons in Prefrontal Cortex

Abstract: Dopamine D2 receptors (D2Rs) play a major role in the function of the prefrontal cortex (PFC), and may contribute to prefrontal dysfunction in conditions such as schizophrenia. Here we report that in mouse PFC, D2Rs are selectively expressed by a subtype of layer V pyramidal neurons that have thick apical tufts, prominent h-current, and subcortical projections. Within this subpopulation, the D2R agonist quinpirole elicits a novel afterdepolarization that generates voltage fluctuations and spiking for hundreds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
237
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(256 citation statements)
references
References 86 publications
(131 reference statements)
16
237
3
Order By: Relevance
“…D3ϩ cells were further distinguished from D2ϩ cells by their axonal projection targets. Although D2ϩ, Type 2 neurons targeted subcortical regions such as the pons and thalamus, D3ϩ neurons had projection patterns more consistent with D1ϩ neurons, including projections to contralateral mPFC and bilateral NAcc and BLA (Dembrow et al, 2010;Gee et al, 2012;Seong and Carter, 2012;Land et al, 2014). Based on these results, we propose that D1R, D2R, and D3R expression defines largely distinct L5 pyramidal cell classes in mPFC, each with unique catecholaminergic responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D3ϩ cells were further distinguished from D2ϩ cells by their axonal projection targets. Although D2ϩ, Type 2 neurons targeted subcortical regions such as the pons and thalamus, D3ϩ neurons had projection patterns more consistent with D1ϩ neurons, including projections to contralateral mPFC and bilateral NAcc and BLA (Dembrow et al, 2010;Gee et al, 2012;Seong and Carter, 2012;Land et al, 2014). Based on these results, we propose that D1R, D2R, and D3R expression defines largely distinct L5 pyramidal cell classes in mPFC, each with unique catecholaminergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…influence resting membrane properties (Dembrow et al, 2010;Gee et al, 2012;Seong and Carter, 2012). We found that D1ϩ, D2ϩ, and D3ϩ neurons had different input resistances when subjected to a Ϫ50 pA current pulse (D1ϩ: 183 Ϯ 5 M⍀, n ϭ 95; D2ϩ: 146 Ϯ 11 M⍀, n ϭ 35; D3ϩ: 212 Ϯ 5 M⍀, n ϭ 188; Kruskal-Wallis, H (2) ϭ 32.91, p ϭ 7 ϫ 10 Ϫ8 ; Wilcoxon's ranksum test, Holm-Sidak correction, D1ϩ vs D2ϩ: z ϭ 3.75, D1ϩ vs D3ϩ: z ϭ Ϫ3.32, D2ϩ vs D3ϩ: z ϭ Ϫ5.01; p Ͻ 0.05) and that D2ϩ cell resting V m was modestly depolarized relative to D3ϩ cells (D1ϩ: Ϫ80.0 Ϯ 0.6 mV; D2ϩ: Ϫ77.9 Ϯ 0.7 mV; D3ϩ: Ϫ80.2 Ϯ 0.4 mV; Kruskal-Wallis, H (2) ϭ 7.26, p ϭ 0.027; Wilcoxon's rank-sum test, Holm-Sidak correction, D2ϩ vs D3ϩ: z ϭ 2.76; p Ͻ 0.05; Fig.…”
Section: D3rs Are Expressed In a Distinct Subset Of Mpfc Pyramidal Cellsmentioning
confidence: 99%
“…A potential answer comes from neuroanatomical studies that have identified separate populations of PFC pyramidal neurons that only express D 1 or D 2 receptors, with relatively few neurons expressing both (Vincent et al, 1993;Gaspar et al, 1995;Santana et al, 2009). Moreover, D 1 -versus D 2 -expressing cells display distinct neurophysiological properties and, in some instances, different subcortical projection targets (Gaspar et al, 1995;Gee et al, 2012;Seong and Carter, 2012). This neuroanatomical framework leaves open the possibility that mesocortical DA may act on separate networks of neurons that are modulated by D 1 or D 2 receptor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found that D2Rs are selectively expressed within thick-tufted, subcortically projecting (SC) L5 pyramidal neurons, which exhibit prominent hyperpolarization-activated cationic current (I h ) (Gee et al, 2012). We found that, in this population, pharmacological activation of D2Rs by the agonist quinpirole elicits a profound afterdepolarization (ADP) following depolarizing current injection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our laboratory and others have shown that, in the mouse mPFC, three major subtypes of dopamine receptors (D1Rs, D2Rs, and D3Rs) are differentially expressed by distinct subtypes of layer 5 (L5) pyramidal neurons (Gee et al, 2012;Seong and Carter, 2012;Clarkson et al, 2017). Specifically, we found that D2Rs are selectively expressed within thick-tufted, subcortically projecting (SC) L5 pyramidal neurons, which exhibit prominent hyperpolarization-activated cationic current (I h ) (Gee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%